Cannabis Glandular Trichomes: A Cellular Metabolite Factory - Tanney, Cailun A. S.; Backer, Rachel; Geitmann, Anja; Smith, Donald L. (Frontiers in Plant Science, 2021)
Cannabis has been legalized for recreational use in several countries and medical use is authorized in an expanding list of countries; markets are growing internationally, causing an increase in demand for high quality products with well-defined properties. The key compounds of Cannabis plants are cannabinoids, which are produced by stalked glandular trichomes located on female flowers. These trichomes produce resin that contains cannabinoids such as tetrahydrocannabinolic acid (THCA) and cannabidiolic acid (CBDA), and an array of other secondary metabolites of varying degrees of commercial interest. While growing tend to focus on improving whole flower yields, our understanding of the “goldmines” of the plant – the trichomes – is limited despite their being the true source of revenue for a multi-billion-dollar industry. This review aims to provide an overview of our current understanding of cannabis glandular trichomes and their metabolite products in order to identify current gaps in knowledge and to outline future research directions.